2009
DOI: 10.1007/s00213-009-1535-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with escitalopram but not desipramine decreases escape latency times in a learned helplessness model using juvenile rats

Abstract: The learned helplessness model with PND 21 rats predicts the efficacy of escitalopram and the lack of efficacy of desipramine seen in the treatment of pediatric depression. These findings suggest that the use of PND 21 rats in a modified learned helplessness procedure may be a valuable model of human pediatric depression that can predict pediatric antidepressant efficacy and be used to study antidepressant mechanisms involved in pediatric depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Because previous work has shown that the SSRIs citalopram or escitalopram can reverse the behavioral effects of chronic stress ( e.g. Bhagya et al, 2011; Bondi et al, 2008; Jayatissa et al, 2006; Overstreet et al, 2004; Reed et al, 2009), we sought to determine whether escitalopram could reverse the behavioral consequences of CeA CRF-OE. We hypothesized that CeA CRF-OE would directly elevate behavioral measures of anxiety and that, without the ability to decrease CeA CRF expression, escitalopram would have limited efficacy unless escitalopram was able to act downstream of postsynaptic CRF neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous work has shown that the SSRIs citalopram or escitalopram can reverse the behavioral effects of chronic stress ( e.g. Bhagya et al, 2011; Bondi et al, 2008; Jayatissa et al, 2006; Overstreet et al, 2004; Reed et al, 2009), we sought to determine whether escitalopram could reverse the behavioral consequences of CeA CRF-OE. We hypothesized that CeA CRF-OE would directly elevate behavioral measures of anxiety and that, without the ability to decrease CeA CRF expression, escitalopram would have limited efficacy unless escitalopram was able to act downstream of postsynaptic CRF neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The injection volume was 1 ml/kg of body weight. The doses for drugs were chosen based on effective doses used in our previous behavioral observations: NAC (100 mg/kg) (Smaga et al 2012) and URB597 (Adamczyk et al 2008) as well as in other literature findings on IMI (15 mg/kg) (Tokita et al 2012), ESC (10 mg/kg) (Reed et al 2009), and TIA (10 mg/kg) (Whitton et al 1991). …”
Section: Methodsmentioning
confidence: 99%
“…The rats were initially placed in 2 groups; a tested control (TC) group, which is restrained with electrodes attached to the tail but not shocked, and an inescapably stressed group (TSS). Twenty-four hours after restraint with or without TSS exposure, rats were divided in two sets, one set of rats tested for escape behavior using a shuttle-box test [23, 24], while the other set of rats were sacrificed before being tested for escape behavior.…”
Section: Methodsmentioning
confidence: 99%